ASSAY OF ANAEMIA DURING INDUCED HYMENOLEPIASIS IN MICE AND RESTORATION WITH PRAZIQUANTEL - J. PARVATHI; ARUNA KAREMUNGIKAR (The Bioscan, 2012)
Helminth infections, the major parasitic diseases, affect the general health and productivity of adults, mental and physical growth of malnourished children, mostly in the tropics. The study of helminth-induced anemia has not been extensive, although this consequence of parasitism is not uncommon. The present study involves the evaluation of haematological alterations induced in the laboratory mouse, Mus musculus, infested with the intestinal helminth, Hymenolepis nana by the estimation of blood parameters in an automatic coulter counter. Using these parameters, the blood indices mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC) were calculated to interpret the extent and type of the resulting anaemia. The healing effects of the broad-spectrum anthelmintic praziquantel in restoring normal haematology in the traumatized host are also envisaged.